Acquiring skills : market failures, their symptoms and policy responses - Booth, Alison L. [Herausgeber]; Snower, Dennis J. [Herausgeber] (Cambridge Univ. Press, 1996)
"This book has three interrelated purposes. The first, addressed in Part I, provide major reasons why the free market system may fail to provide adequate incentives for the acquisition of skills. For a long time mainstream economists used to believe that the Invisible Hand would invariably lead people to acquire skills as long as the resulting benefit to society exceeded the associated cost. Over the past decade, however, there has been an emerging realization that this is not so. But the new research is fragmented and the old views die hard. This book attempts to bring some of the most interesting and potentially significant market failures in providing skills...under one cover. In doing so, is sets the stage for reasoned debate about government provision and regulation of training. The second purpose, adressed in Part II, is to examine some salient empirical consequences of the problems using a portfolio of examples concerning the effects of different types of - skills gaps-,that is, deficiencies in the availability of trained employees. For brevity, these examples focus mainly on the UK and a limited number of other European countries. The consequences range from microeconomic problems, such as deficient productivity, insuffcient innovation, and specialization in the produktion of goods that are of insufficient quality, to macroeconomic problems such as poor export performance, and insufficient competitiveness. They are meant to tell us what sorts of things to look for when we seek to assess whether a country-s economic performance is impeded by insufficient produktion of skills. And the third purpose, addressed in Part III, is to give a preliminary account of what policy initiatives are appropriate for dealing with skills gaps and their consequences. This is based not just on an analysis of market failures, but also on a recognition of important government failures in the process of policy design and implementation." (author-s abstract, IAB-Doku) ((en)) Das aus einer vom britischen Arbeitsministerium geförderten Konferenz unter der Schirmherrschaft des Centre for Economic Policy Research hervorgegangene Buch verfolgt die miteinander verbundene Ziele: Im ersten Teil wird untersucht, warum das System der freien Marktwirtschaft u.U. bei der Aufgabe versagt, angemessene Anreize zum Erwerb von Qualifikationen vorzusehen. In Teil 2 werden mehrere wichtige Folgen dieser Probleme anhand von Beispielen für Auswirkungen verschiedener Arten von Qualifikationsdefiziten, d.h. von Mängelsituationen bei der Verfügbarkeit ausgebildeter Fachkräfte untersucht. Diese Beispiele beziehen sich hauptsächlich auf Grossbritannien und eine beschränkte Zahl anderer europäischer Länder. Dabei spielen Zusammenhänge mit unzureichender Produktivität, Innovation, Spezialisierung der Warenproduktion, Exportleistungen und Wettbewerbsfähigkeit eine Rolle. In Teil 3 Werden bildungspolitische Implikationen der Bewältigung von Qualifikationsdefiziten erörtert, wobei nicht nur Versäumnisse des Marktes, sondern auch Versäumnisse von Staat und Regierung bei Konzeption und Umsetzung von Bildungspolitik analysiert werden. (IAB)
Erwerb von Qualifikationen : Marktmängel, ihre Symptome und Anworten der Politik
Keywords: G 1.2.3.1 Potenziale; G 2.3.4 Qualifikationswandel; G 1.2.3.2 Anforderungen & Bedarfe; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; S 2.3 Berufsbildungspolitik; S 4.3.6 Human Capital; G 1.3.1 Bildungsangebot & -nachfrage; G 2.3.5 Wirtschaftsstrukturwandel; S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; G 2.1 Globalisierung; I 2.2.1 Westeuropa; Qualifikation; Qualifikationsbedarf; Qualifikationsdefizit; Qualifikationsvermittlung; Bildungspolitik; Humankapital; Nachfrage; Wirtschaftsstruktur; Strukturwandel; Berufsausbildung; Betriebliche Berufsausbildung; Berufliche Weiterbildung; Betriebliche Weiterbildung; Qualifikationsstruktur; Wettbewerbsfähigkeit; Quantitative Angaben; Großbritannien